Stealth Vaping Among College Students on Four Geographically Distinct Tobacco-Free College Campuses: Prevalence and Practices. Issue 3 (23rd July 2021) - Russell, Alex M; Yang, Meng; Barry, Adam E; Merianos, Ashley L; Lin, Hsien-Chang
Abstract: Introduction: To offset tobacco use among college students, many universities have implemented tobacco-free campus policies. Given how easily e-cigarette users can discreetly vape in places where it is prohibited without being detected (ie, stealth vape), it is important to assess whether students are subverting these policies. This study examined the prevalence of stealth vaping on-campus among students at multiple universities, including frequency and methods for stealth vaping. Aims and Methods: A convenience sample of college students was obtained from four geographically distinct, large, public universities with established policies prohibiting all forms of tobacco use on campus. Participants ( N = 863 current e-cigarette users) reported on demographics and e-cigarette use. Those who previously stealth vaped on-campus ( n = 422) completed additional questions, including common locations, techniques, and devices/e-liquids used for stealth vaping. Results: Nearly half (48.9%) of past 30-day e-cigarette users reported previously stealth vaping on-campus. Among stealth vapers, 48.1% owned a smaller device for stealth vaping and 38.9% used e-liquids with low visibility vapors. Common on-campus stealth vaping locations included bathrooms, libraries, parking garages, and classrooms. Techniques used for stealth vaping included deep inhale, blowing a hit into one's clothes, and swallowing a hit. Conclusions: A large percentage of respondents commonly violated campus tobacco-free policies by stealth vaping. For such policies to be effective at reducing on-campus e-cigarette use, there is a need for enhanced monitoring and enforcement. More research is needed to better understand factors influencing stealth vaping behaviors and public health implications. Implications: This sample of college student e-cigarette users commonly violated campus smoke- and tobacco-free policies by stealth vaping on campus. Respondents used a range of methods (eg, smaller device and low visibility e-liquids) and locations (eg, bathrooms, libraries, and parking garages) for stealth vaping. If campus policies are to be effective at reducing on-campus e-cigarette use, there is a need for enhanced monitoring and enforcement. E-cigarette devices specifically designed and marketed to facilitate stealth vaping (eg, resembling USB flash drives and pens) may require regulatory action. More research is needed to better understand factors influencing stealth vaping behaviors and public health implications.